Early calcineurin-inhibitor to belatacept conversion in steroid-free kidney transplant recipients - Tawhari, Ibrahim; Hallak, Patrick; Bin, Sofia; Yamani, Fatmah; Safar-Boueri, Maria; Irshad, Aazib; Leventhal, Joseph; Ansari, Mohammed Javeed; Cravedi, Paolo; Gallon, Lorenzo (Frontiers in Immunology, 2022)
Background Belatacept (Bela) was developed to reduce nephrotoxicity and cardiovascular risk that are associated with the chronic use of Calcineurin inhibitors (CNIs) in kidney transplant recipients. The use of Bela with early steroid withdrawal (ESW) and simultaneous CNI avoidance has not been formally evaluated. Methods At 3 months post-transplant, stable kidney transplant recipients with ESW on Tacrolimus (Tac) + mycophenolate (MPA) were randomized 1:1:1 to: 1) Bela+MPA, 2) Bela+low-dose Tac (trough goal <5 ng/mL), or 3) continue Tac+MPA. All patients underwent surveillance graft biopsies at enrollment and then at 12, and 24 months post-transplant. Twenty-seven recipients were included; 9 underwent conversion to Bela+MPA, 8 to Bela+low-dose Tac and 10 continued Tac+MPA. Serial blood samples were collected for immune phenotyping and gene expression analyses. Results The Bela+MPA arm was closed early due to high rate of biopsy proven acute rejection (BPAR). The incidence of BPAR was 4/9 in Bela+MPA, 0/8 in Bela+low dose Tac and 2/10 in Tac+MPA, P= 0.087. The Bela+low-dose Tac regimen was associated with +8.8 mL/min/1.73 m2 increase in eGFR compared to -0.38 mL/min/1.73 m2 in Tac+MPA, P= 0.243. One graft loss occurred in the Bela+MPA group. Immunophenotyping of peripheral blood monocyte count (PBMC) showed that CD28+CD4+ and CD28+CD8+ T cells were higher in Bela+MPA patients with acute rejection compared to patients without rejection, although the difference did not reach statistical significance. Conclusions Our data indicate that, in steroid free regimens, low-dose Tac maintenance is needed to prevent rejection when patients are converted to Bela, at least when the maneuver is done early after transplant.